1984
DOI: 10.1192/bjp.144.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ventricular Enlargement in Non-Genetic Schizophrenia: a Controlled Twin Study

Abstract: In a group of schizophrenics of twin birth, no evidence of ventricular enlargement was found where there was a family history of major psychiatric disorder. Among those schizophrenics without such a family history, cerebral ventricular size was significantly increased (P less than 0.01), and there was also evidence of birth complications. Among normal control twins, those who reported complicated births had significantly larger ventricles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(61 citation statements)
references
References 3 publications
2
59
0
Order By: Relevance
“…The twin studies consistently report lateral ventricular enlargement as a difference between affected and nonaffected twins (Reveley et al 1982(Reveley et al ,1984Suddath et al 1990). Similar to our findings, the magnetic resonance imaging (MRI) twin study noted differences in the temporal lobes (Suddath et al 1990).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The twin studies consistently report lateral ventricular enlargement as a difference between affected and nonaffected twins (Reveley et al 1982(Reveley et al ,1984Suddath et al 1990). Similar to our findings, the magnetic resonance imaging (MRI) twin study noted differences in the temporal lobes (Suddath et al 1990).…”
Section: Discussionsupporting
confidence: 89%
“…Investigating family members has the considerable advantage of optimal matching of affected (psychotic) and unaffected (control) individuals. Brain imaging studies using sibling pairs and twins have indicated that ventricular enlargement and reduction in the size of temporal lobe structures occurs in the affected individuals (De-Lisi et al 1986;Reveley et al 1982Reveley et al , 1984Suddath et al 1990;Weinberger et al 1981). A complementary strategy is to study multigenerational families in which two or more members have schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…[160][161][162] Sporadic cases are more likely to be winter-born 159,163,164 and have more electroencephalographic (EEG) abnormalities 153 and enlarged ventricles on CT scan or MRI. 152,165,166 Familial cases, on the other hand, have more neurological signs, 164,[167][168][169] poorer sustained attention performance; 170 cortical abnormalities on MRI 171 and reduced temporoparietal resting regional blood flow. 172 By and large, the F/S classification has not been successful in identifying homogeneous phenotype groups for genetic research.…”
Section: Subtypes Based On Putative Genetic Indicatorsmentioning
confidence: 99%
“…One early study [97] compared monozygotic and dizygotic twins for ventricular size and found high heritability.…”
Section: Endophenotypesmentioning
confidence: 99%